Marine litter in submarine canyons: A systematic review and critical synthesis - Hernandez, Ivan; Davies, Jaime S.; Huvenne, Veerle A. I.; Dissanayake, Awantha (Frontiers in Marine Science, 2022)
The presence of marine litter is of concern in submarine canyons, although research in this area is still in its infancy. A critical synthesis and literature review selecting studies with primary data of benthic marine litter at depths of over 50 m revealed important gaps in the knowledge, with information on the impact of macroplastics in deep-sea environments still scarce. Less than 1% of medium to large submarine canyons mapped have been studied in any measure for marine litter, with over 91% of the canyon studies located in European waters. Imaging techniques are now the main tools used for sampling, overtaking trawling methods despite the continued growth of the latter for marine litter deep-sea research. Enumeration of litter was diverse with over 75% using abundance for quantification. Despite the existence of litter protocols available for deep-sea environments, over 73% of studies did not use any. There was no standardisation in the implementation of established classification protocols, which were either not used in full or were customised in part. Fishing-related categories do not feature as a top-level category in the classification hierarchy in any of the protocols, yet over 50% of publications featured fishing materials as a main category, pointing to a more intuitive activity-based categorisation of litter instead of a materials-led approach from the established protocols. Furthermore, interactions between litter and the surrounding environment and biota are very much underreported with little or no consensus between how the data are analysed and expressed. There were no discernible patterns between litter density, composition and broad geographical location of canyons, with individual topographical characteristics, hydrodynamic regimes and anthropogenic activities being determining factors in how submarine canyons are affected by litter. Overall, there is no apparent framework to allow comparison of studies and due to the different methods of identifying, enumerating, quantifying and classifying marine litter, or lack of data on position and morphological setting within the canyon system. The evidence provided within highlights a ‘call to action’ for an urgent need to standardise and unify methodologies with new or established protocols to fully understand the impact of marine litter in submarine canyons.